Effects of homocysteine on eNOS and DDAH gene expression levels in primary human umbilical endothelial cell culture [Homosisteinin insan göbek kordon ven endotel hücre kültüründe eNOS ve DDAH gen ekspresyonlari üzerine etkisi] - (:unkn) unknown (My University, 2007)
Aim: Elevated plasma homocysteine levels are independent risk factors for myocardial infarction, stroke and peripheral vascular disease. The aim of this study was to investigate effects of homocysteine on nitric oxide (NO) synthesis, bioavailability and degradation by analysis gene expression levels of endothelial nitric oxide synthase (eNOS) and dimethylarginine dimethylaminohydrolase (DDAH) and also NO levels in endothelial cell line. Material and Methods: Human umbilical vein endothelial cell culture (HUVEC) was performed and incubated with various homocysteine concentrations (10μM, 50μM, 100μM, 500μM, 1000μM). After that, total RNA was extracted from these cells and converted to cDNA. These cDNA samples were amplified with PCR for eNOS and DDAH genes. Then the products were run in agarose gel electrophoresis and analysed for densitometric measurement by gel imaging system. In addition, NOx was analysed in cell culture mediums with electrochemiluminesans method.